2000
DOI: 10.1046/j.1365-2346.2000.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia for Proteus syndrome

Abstract: A 4-month-old boy with Proteus syndrome underwent a successful operation for a left abdominal mass due to hydroureter and hydronephrosis with left ureterovesical stenosis. The operation lasted 4.5 h under general anaesthesia; there were no anaesthetic complications. There is only one previous report on anaesthesia in a patient with Proteus syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…17 Additionally, women with Proteus syndrome may have obstructive or restrictive lung disease which further increases their risk during general anaesthesia. 18 Our patient did not have any obstruction or restrictive lung disease.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…17 Additionally, women with Proteus syndrome may have obstructive or restrictive lung disease which further increases their risk during general anaesthesia. 18 Our patient did not have any obstruction or restrictive lung disease.…”
Section: Discussionmentioning
confidence: 57%
“…Vertebral distortion including fixed flexion, limited range of mobility and torticollis may also be present, and therefore difficulties in intubation during general anaesthesia should be anticipated. 18 Meningiomas and hyperostosis of cranial and facial bones are commonly found in Proteus syndrome. One retrospective cohort study found these to be present in 6.5% and 48%, respectively, in a group of 61 women with Proteus syndrome.…”
Section: Anaesthetic Considerationsmentioning
confidence: 99%
“…7,9 Equipment for a difficult airway should be available immediately whenever a patient with Proteus syndrome is to receive anaesthesia. 9,10 For patients with preoperative symptoms or signs of upper airway obstruction, sedative premedication and perioperative opioids should be avoided and the patient should be nursed in a high care unit postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Although muscular overgrowth occurs, Proteus syndrome is not regarded as a muscular disease or a malignant hyperthermia risk factor. 6,10 The high incidence of vascular, skeletal and soft tissue abnormalities has made the placing of neural blocks difficult. However, the growing experience with ultrasound-guided regional anaesthesia could change this obstacle as structures can now be visualised and neural blocks safely performed.…”
Section: Discussionmentioning
confidence: 99%
“…Ceyhan et al. reported a 4‐year‐old boy with PS who had general anesthesia for an abdominal mass (21). Pradhan et al.…”
Section: Discussionmentioning
confidence: 99%